Exposición y crítica de la ética de Clemente de Alejandría - Buganza, Jacob (Sapientia, 2010)
In this article, the author discusses the ethics of Clement of Alexandria using mainly El Pedagogo and El Protréptico. Gives special importance to concepts such as salvation, free will, advice, imitation, among others. Then, the author makes a critical thesis looking for validity to the approach of contemporary ethics. But it is important to remember that ethics naturally resorts to the tradition, where it feeds to develop its philosophical reflection. In other words, ethics does not start from a vacuum but within a tradition, one of whose representatives and builders in the context of the Western world is Clement of Alexandria.